2021
DOI: 10.1021/acsami.1c00700
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Photostability of Inverted Nonfullerene Organic Solar Cells by Using Fullerene Derivative Additives

Abstract: Organic solar cells (OSCs) recently achieved efficiencies of over 18% and are well on their way to practical applications, but still considerable stability issues need to be overcome. One major problem emerges from the electron transport material zinc oxide (ZnO), which is mainly used in the inverted device architecture and decomposes many high-performance nonfullerene acceptors due to its photocatalytic activity. In this work, we add three different fullerene derivativesPC71BM, ICMA, and BisPCBMto an invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 57 publications
0
34
0
4
Order By: Relevance
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 89%
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to the surface defects, ZnO exhibits intense photocatalytic activity, which induces chemical reactions at the ETL/active layer interface, especially when NFAs are used as the acceptors. [16] Such chemical reactions can dominate the degradation process for the NFA based OSCs. [17] Ma et al found that base treatment of ZnO caused poorer performance and accelerated the degradation of NF-OSCs, which was originated from enormous hydroxyl groups on the ZnO film.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…[29] Yang et al reported a series of titanium diisopropoxide bis(acetylacetonate) (TIAA) based ETLs by changing the TA temperatures. [30] With increasing the temperature from 75 to 125 and 200 °C, the WF was lowered from À 3.7 eV of LT TIAA to À 3.9 eV of MT TIAA and À 4.1 eV of HT TIAA, owing to the 16 , denoted as Ti12) Ti atoms in the cores and alkyl groups on the surface as ETLs. [31] These TOCs have precise chemical structures with a single crystal, excellent solubility in methanol, well-aligned WF and could form smooth films on top of the active layer.…”
Section: Metal Chelatesmentioning
confidence: 99%
See 2 more Smart Citations